Facile Synthesis of Sub‐Nanometric Copper Clusters by Double Confinement Enables Selective Reduction of Carbon Dioxide to Methane - Hu, Qi; Han, Zhen; Wang, Xiaodeng; Li, Guomin; Wang, Ziyu; Huang, Xiaowan; Yang, Hengpan; Ren, Xiangzhong; Zhang, Qianling; Liu, Jianhong; He, Chuanxin (Angewandte Chemie International Edition, 2020)
Previous density‐functional theory (DFT) calculations show that sub‐nanometric Cu clusters (i.e., 13 atoms) favorably generate CH4 from the CO2 reduction reaction (CO2RR), but experimental evidence is lacking. Herein, a facile impregnation‐calcination route towards Cu clusters, having a diameter of about 1.0 nm with about 10 atoms, was developed by double confinement of carbon defects and micropores. These Cu clusters enable high selectivity for the CO2RR with a maximum Faraday efficiency of 81.7 % for CH4. Calculations and experimental results show that the Cu clusters enhance the adsorption of *H and *CO intermediates, thus promoting generation of CH4 rather than H2 and CO. The strong interactions between the Cu clusters and defective carbon optimize the electronic structure of the Cu clusters for selectivity and stability towards generation of CH4. Provided here is the first experimental evidence that sub‐nanometric Cu clusters facilitate the production of CH4 from the CO2RR. A facile impregnation‐calcination route has been developed for the general synthesis of various metal clusters, having sizes of about 1.0 nm, by double confinement. The resulting Cu clusters confer a high selectivity for the carbon dioxide reduction reaction with a maximum Faraday efficiency of 81.7 % for methane.